(untitled) (Asian Journal of Medical and Biological Research, 2016)
Fish play a crucial role in the Bangladeshi diet, providing more than 60% of animal source food, representing a crucial source of micro-nutrients and possessing an extremely strong cultural attachment. In this study isolation and identification of Aeromionas hydrophila was done by studying cultural properties, Grams staining and biochemical properties of isolates of diseased indigenous Koi fish (Anabas testudineus) of different upazillas of Mymensingh district. Antibiogram profile of the isolated bacteria was studied by using wide range of commercially available antibiotics. Quantitative study of bacteria isolated from diseased indigenous Koi fish showed variation of number in different organ. Total bacterial load was found to be 1.90 × 105, 1.19 × 105, 3.21 × 105, 2.18 × 106 and 3.14 × 105 cfu/g in lesions; 2.52 × 107, 2.34 × 108, 5.41 × 108, 2.54 × 109 and 5.21 × 109 cfu/g in liver; 2.54 × 108, 2.41 × 108, 1.90 × 107, 3.65 × 107 and 3.45 × 108 cfu/g in spleen; 3.51 × 107, 5.28 × 107, 3.14 × 106, 1.85 × 107 and 4.52× 107 cfu/g in kidney in diseased Koi of Mymensingh sadar, Muktagacha, Tarakanda, Gouripur and Fulpur upazillas, respectively under Mymensingh districts. Aeromonas hydrophila was initially identified by their specific morphological, physiological and biochemical characteristics. Then molecular detection of A. hydrophila was done by PCR. PCR products of desired 760 bp were obtained for A. hydrophila. The results of the antibiotic sensitivity test is exhibited that most of the bacterial samples were sensitive against ciprofloxacin (92%) and levofloxacin (84%), intermediate resistant against gentamicin (40%) and resistant against novobiocin (84%), ampicillin (100%) and penicillin (92%). Asian J. Med. Biol. Res. June 2016, 2(2): 332-340